Functions of a C‐type lectin with a single carbohydrate‐recognition domain in the innate immunity and movement of the red flour beetle, Tribolium castaneum. Issue 1 (16th November 2020) - Li, J.; Bi, J.; Zhang, P.; Wang, Z.; Zhong, Y.; Xu, S.; Wang, L.; Li, B.
Abstract: C‐type lectins (CTLs) are a superfamily of proteins found in almost all vertebrates and invertebrates. They play an important role in innate immune defences, development and epidermal structure. Here, a CTL with one carbohydrate‐recognition domain containing a highly conserved Gln‐Pro‐Asp (QPD) motif was identified in Tribolium castaneum and given the name TcCTL5. Spatiotemporal analyses showed that Tcctl5 was highly expressed in the late pupa stage and mainly existed in the central nervous system and haemolymph. The transcript level of Tcctl5 was prominently induced after bacterial infection. Recombinant TcCTL5 proteins (rTcCTL5) were found to bind to lipopolysaccharide, peptidoglycan and tested bacteria and induce microbial agglutination in the presence of Ca 2+ . Interestingly, when Tcctl5 was knocked down, the transcript level of antimicrobial peptides (AMPs) ( attacin1, defensins3, coleoptericin1 and cecropins3 ) was prominently downregulated after induction with Gram‐negative Escherichia coli . More interestingly, Tcctl5 was knocked down, leading to increased mortality and loss of locomotor activity, which exhibited less travel distances among early adults. These results demonstrate that Tcctl5 plays an important role in the innate immune reaction and the movement of T. castaneum . Thus, it may represent an alternative molecular target for pest control and thus reduce the use of pesticides in agricultural production.